Combination metformin and liraglutide in PCOS: clinical efficacy in women and preclinical insights from gut microbiome modulation in rats - Long, Xue-Feng; Fang, Yu-Qing; Li, Yan-Hui; Li, Jing-Yi; Wang, Xiu-Ping; Wang, Xiao-Li; Zhang, Ling; Liu, Yi (Frontiers in Endocrinology, 2025)
BackgroundMetformin and liraglutide have been gradually used in the treatment of polycystic ovary syndrome (PCOS) due to their metabolic benefits, but also with some adverse reactions. Evidence suggests that gut microbiota imbalance plays an important role in the pathogenesis of PCOS. This study comprised a clinical trial to evaluate the efficacy of metformin, liraglutide, and their combination in PCOS women, and a parallel animal experiment to explore the potential involvement of gut microbiota.MethodsIn an open-label randomized controlled trial, sixty overweight/obese women with PCOS were randomized to: the MET group received oral metformin (0.85 g twice daily; n=20), the LIRA group received subcutaneous liraglutide (1.2 mg once daily; n=20), and the COM group received both treatments (n=20) for 12 weeks. In a separate animal study, female Sprague-Dawley rats were divided into five groups: (1) PCOS model group (letrozole 1 mg/kg orally); (2) MET group (letrozole + metformin 200 mg/kg orally); (3) LIRA group (letrozole + liraglutide 0.2 mg/kg subcutaneously); (4) COM group (letrozole + metformin + liraglutide at above doses); and (5) healthy controls (no treatment). All treatments lasted 4 weeks.ResultsIn the clinical trial, women in MET, LIRA, and COM groups showed significant reductions in body weight, blood glucose, blood lipid, and the LH/FSH ratio. Notably, body weight, BMI, visceral fat area, and body fat percentage decreased more significantly in the COM group than in the MET group (P<0.05). Compared with the MET group, the COM group was more effective in reducing free testosterone (P=0.01). In the animal experiment, the body weight, estrus cycle, and ovarian morphology of rats in the COM group were significantly improved. Letrozole-induced PCOS rats showed intestinal flora disorder, which was improved by metformin, liraglutide, and their combination by altering the alpha and beta diversity and relative abundance of the gut microbiota.ConclusionMetformin combined with liraglutide significantly improved metabolic and endocrine characteristics in PCOS women. The associated amelioration of gut microbiota dysbiosis in PCOS rats suggests a potential mechanistic link, which warrants verification in future clinical studies.